Recovery from COVID-19: a sprint or marathon? 6-month follow-up data from online long COVID-19 support group members. Issue 2 (24th May 2021) - Vaes, Anouk W.; Goërtz, Yvonne M.J.; Van Herck, Maarten; Machado, Felipe V.C.; Meys, Roy; Delbressine, Jeannet M.; Houben-Wilke, Sarah; Gaffron, Swetlana; Maier, Dieter; Burtin, Chris; Posthuma, Rein; van Loon, Nicole P.H.; et al.
Background: It remains unknown whether and to what extent members of online "long COVID" peer support groups remain symptomatic and limited over time. Therefore, we aimed to evaluate symptoms in members of online long COVID peer support groups up to 6 months after the onset of coronavirus disease 2019 (COVID-19)-related symptoms. Methods: Demographics, symptoms, health status, work productivity, functional status and health-related quality of life were assessed about 3 and 6 months after the onset of COVID-19-related symptoms in members of online long COVID peer support groups. Results: Data from 239 patients with a confirmed COVID-19 diagnosis (83% women; median (interquartile range) age 50 (39–56) years) were analysed. During the infection, a median (interquartile range) of 15 (11–18) symptoms was reported, which was significantly lower 3 and 6 months later: 6 (4–9) and 6 (3–8), respectively (p<0.05). From 3 to 6 months follow-up, the proportion of patients without symptoms increased from 1.3% to only 5.4% (p<0.001). Patients also reported a significantly improved work productivity (work absenteeism and presenteeism: 73% versus 52% and 66% versus 60%, respectively), self-reported good health (9.2% versus 16.7%), functional status (mean±sd Post-COVID-19 Functional Status scale: 2.4±0.9 versus 2.2±1.0) and health-related quality of life (all p<0.05). Conclusion: Although patients with confirmed COVID-19, who were all members of online long COVID peer support groups, reported significant improvements in work productivity, functional status and quality of life between 3 and 6 months follow-up, these data clearly highlight the long-term impact of COVID-19, as approximately 6 months after the onset of COVID-19-related symptoms a large proportion still experienced persistent symptoms, a moderate-to-poor health, moderate-to-severe functional limitations, considerable loss in work productivity, and/or an impaired quality of life. Action is needed to improve the management and healthcare of these patients. Patients who are members of online #longCOVID peer support groups may still experience persistent symptoms about 6 months after the onset of symptoms, which can affect work productivity, functional status and quality of life https://bit.ly/3vxPF2b